Mathematics Student Decision Making Based on Self-Efficacy in Probabilistic Thinking - Ali Shodiqin; Sukestiyarno Sukestiyarno; Wardono Wardono; Isnarto Isnarto (International Conference on Science, Education, and Technology, 2022)
One thing that needs to be considered in the thinking process is the ability to make decisions. Decision-making includes probabilistic thinking. Decision-making is usually done after going through a series of processes. This study discusses how mathematics student decision-making is based on self-efficacy in probabilistic thinking. This research is descriptive qualitative research. The validity of research data with triangulation techniques. The results show that decision-making in probabilistic thinking requires a series of processes, namely understanding the problem, having initial intuition, choosing the right strategy, doing numeracy, then evaluating, and then making a decision. For subjects who have high self-efficacy, the subject makes decisions that fulfill all the elements in decision making. Subjects with self-efficacy are in the decision-making process, the use of numerical concepts is still not right, but the other elements have been met. For subjects with low self-efficacy abilities, they are still less precise in initial intuition, numeration, and final evaluation so the decision making is still not right.